2014
DOI: 10.1148/radiol.13131605
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave Amplitudes Measured with Cardiac MR Elastography for Diagnosis of Diastolic Dysfunction

Abstract: LV SWA measured with cardiac MR elastography provides image contrast sensitive to myocardial relaxation abnormalities and shows significantly lower values in patients with diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 29 publications
(31 reference statements)
1
41
0
Order By: Relevance
“…We believe this is because the systolic stiffness increases more than the diastolic stiffness, which is due to the heart having to work harder because of increase in afterload during systole associated with changes in aortic compliance with increasing age(35). Furthermore, Elgeti, et al (21) showed no correlation of CMRE-derived displacements (i.e. stiffness) to age which agrees with our results.…”
Section: Discussionsupporting
confidence: 92%
“…We believe this is because the systolic stiffness increases more than the diastolic stiffness, which is due to the heart having to work harder because of increase in afterload during systole associated with changes in aortic compliance with increasing age(35). Furthermore, Elgeti, et al (21) showed no correlation of CMRE-derived displacements (i.e. stiffness) to age which agrees with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Other techniques are now under development to estimate myocardial shear elasticity/viscoelasticity [2, 5, 13, 19, 29, 38, 42, 43]; however, transthoracic measurements are still technically challenging and require special equipment or are based on magnetic resonance imaging, which has limited availability. Conversely, TDI is now available on all commercial systems for cardiac imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance elastography (MRE) has been used to measure shear waves from an external vibration source to evaluate wave propagation in the myocardial wall (Kolipaka et al ., 2010; Kolipaka et al ., 2011; Sack et al ., 2009; Elgeti et al ., 2009; Tzschätzsch et al ., 2012; Elgeti et al ., 2012; Elgeti et al ., 2014). The frequencies used for generating the shear waves for these cardiac applications using MRE typically range from 24-200 Hz.…”
Section: Introductionmentioning
confidence: 99%